Second Five Year Plan District Plan 1958-59 Karimnagar District - Government of Andhra Pradesh (Government of Andhra Pradesh, 1958)
The District Plan for 1958–59 under the Second Five-Year Plan presents a comprehensive blueprint for the socio-economic advancement of Karimnagar District, integrating agricultural modernization, infrastructure development, social welfare, and industrial promotion within a coordinated planning framework. With agriculture forming the backbone of the district’s economy, substantial allocations were directed toward improved seed distribution, establishment of seed farms, repair of irrigation tanks, and expansion of minor irrigation to enhance productivity and stabilize rural livelihoods. Infrastructure initiatives emphasized road construction, railway improvements, telecommunication expansion through new Public Call Offices and telephone exchanges, and modernization of level crossings and passenger amenities to strengthen regional connectivity and economic integration. The plan also prioritized human development through investments in education, teacher training, primary health centres, hospital upgrades, maternal and tuberculosis control programs, and targeted welfare schemes for Scheduled Castes and Scheduled Tribes. Support for small-scale and cottage industries, including traditional crafts such as silver filigree, aimed to diversify income sources and encourage cooperative enterprise. Governance and implementation were overseen by a structured District Planning and Development Committee comprising administrative officials and elected representatives to ensure coordinated execution. With a proposed outlay of approximately Rs. 34 crores, the plan reflects an integrated and participatory approach to district-level planning, seeking to elevate living standards, enhance public services, and lay the foundation for sustainable rural and urban development in Karimnagar.
Planning and Development Department Andhra Pradesh
Planning and Development Department Andhra Pradesh
Keywords: State Plan; Karimnagar District; Agricultural Development; Minor Irrigation; Infrastructure Expansion; Rural Communication; Public Health Services; Educational Development; Small Scale Industries; Scheduled Castes and Scheduled Tribes Welfare; Railway Modernization; District Planning Committee